Effect of preputial washing on seminal characteristics and bacterial load in buck semen - SINHA, N K; GUPTA, V K (The Indian Journal of Animal Reproduction, 2003)
Semen was collected through artificial vagina from 10 Sirohi bucks 20 minutes after washing or preputial sheath with 0.9% sterile saline solution in one week and without washing in the next week. A total of 60 ejaculates comprising 30 each for washing and without washing were used to study the seminal characteristics and bacterial load. There was no significant effect of washing of preputial sheath on reaction time and seminal characteristics like consistency, mass motility, dead spermatozoa(%) and abnormal spermatozoa. Bacterial load was significantly (p<0.05) more (23.55xl02CFU /ml in 100 dilution) in unwashed group than in washed group (19.95xl02 CFU/rnl).